3D Metric approach to study the factors affecting student’s psychology on Education - Kumudavalli, MV; Kulkarni, Anagha Shailesh; Ambrish, G (International Journal of Computer Sciences and Engineering, 2019)
Student psychology in general terms is the study of development of child in terms of his/her abilities. Seeking the evidence on the problems of relative effects i.e., personal and environmental, upon the child’s ability and consideration of adjustment of the child to the circumstances. Every child is special in his/her own way. The mind-set of the child depends and grows upon the instances which the child undergoes i.e. either by personal problem or say environmental effect. Both the internal, as well as external factor plays a major role in building up the personality and attitude of the child. Student’s attitude may differ due to the circumstance they undergo on daily basis. This paper deals with a 3D metric (Internal factor, External factor, Self interest) which plays a key role in analyzing the psychology of the student pertaining to education. The analysis is done through questionnaire consisting of factors affecting the study and a parametric way of scoring is done to the answers which help the student in finding the optimum way out to address the factors affecting them.